Gene delivery strategies targeting stable atheromatous plaque. - Van-Assche, T; Huygelen, V; Crabtree, M; Antoniades, C (2013)
Conventional therapeutic options to treat chronic angina pectoris are pharmacological interventions, coronary bypass surgery (CABG) and percutaneous coronary intervention (PCI). In animal models, it was shown that gene delivery strategies harbour an exciting potential to support and maybe even replace conventional anti-angina treatments, but the translation of the basic science to clinical practise appears problematic. Gene therapy targeting key elements of neointima formation (e.g. cell cycle regulators, metalloproteinases, inflammation and oxidative stress) reduces vein graft and stent failure in experimental models. Additionally, systemic gene delivery of genes targeting NO production, oxidative stress, inflammation and foam cell formation has been shown to prevent atherosclerosis in different animal models. During CABG the vein graft can be transfected ex vivo and during PCI, a stent carrying transfection vectors can be deployed. Both strategies result in the induction of local transgene expression at the site of interest. This limits unwarranted transgene expression and the toxicity seen with systemic gene delivery. However, with the development of new transfection vectors, able to induce local transgene expression without detrimental side effects, systemic anti-inflammatory and anti-oxidative, gene delivery could be a powerful tool in secondary prevention.